Model of evolution of scheduling sub-channels to improve quality of service in wimax network - AL-Janabi, Haider Dheyaa; AL-Janabi, Hussam Dheyaa; Al-Dulaimi, Aymen Mohammed (Eastern-European Journal of Enterprise Technologies, 2015)
Based on the Flaws of the known mechanisms of the frequency resources scheduling in the download channel, the problem, which is raised in this paper is assuring QoS by available resources which directly influence the quality of the equipment design. The WiMAX resource allocation algorithms determine which users to schedule, how to allocate subcarriers to them, and how to determine the appropriate power levels for each user on each subcarrier. We present a brief survey of recent scheduling research. The goals of scheduling are to achieve the optimal usage of resources, to assure the QoS guarantees, the mathematical model introduced by a number of linear and nonlinear conditions-limitations is analyzed in this research. Therefore, the model that consists in the statement of the sub-channels scheduling task is proposed. This model gives a solution of tasks of rescheduling of the accessible capacity of the download channel of the WiMAX technology for the information transmission in the direction of users stations, taking into account their territorial remoteness.